Noncontact Multiple Heartbeats Detection and Subject Localization Using UWB Impulse Doppler Radar - Lingyun Ren; Yun Seo Koo; Haofei Wang; Yazhou Wang; Quanhua Liu; Fathy, Aly E. (IEEE microwave and wireless components letters, 2015)
In this letter, a phase-based algorithm based on a logarithmic method, applicable to UWB radars and suitable to real-time monitoring, is proposed to detect the phase variations of reflected pulses caused by the tiny cardiac motions. Compared with conventional FFT vital signs detection method, this algorithm demonstrates advantage in respiration harmonics suppression and avoidance of intermodulation between respiration and heartbeat signals. Furthermore, it is experimentally shown that UWB Doppler radar is capable of multiple heartbeats detection and subject identification/localization.